What our colleagues says.... Basic anesthetic considerations in neurosurgery - Arvind Chaturvedi (Indian Journal of Neurosurgery)
Rapid development in neurosurgical practice poses new challenges for anaesthesiologists requiring search for newer and safer anaesthetic agents and modification in basic anaesthetic techniques. The present article describes the basic neuroanaesthetic considerations and some of the newer developments in anaesthetic drugs and techniques which are important during neurosurgical practice.